Igbu-Efi: Indigenous Practice and Politics of After-Death in Igbo Culture Area - Nwankwo, Elochukwu A; Anozie, Okechukwu (Review of Knowledge Economy, 2014)
Indigenous practice and culture are among the things that make the Igbo distinctive from their adjoining neighbours. Much value is attached to indigenous practice and most adults are expected to be true custodians. In the funeral process of the Igbo, some aspects are given peculiar attention and interpretation. This is mostly attached to the second burial ceremonies where some indigenous practices are sacrosanct for the bidding of final farewell to the departed and the celebration that follows afterwards. The implication is that the act is a necessary distraction and economic desecrate in those Igbo culture areas where it is practiced. This paper examines this indigenous practice in the Igbo culture area; origin, reasons, implications, challenges and prospects, with a relevant case study. The methodology is purely ethnographic with constructive interview sessions organized amongst randomly selected key informants from Anambra, Enugu, Imo, Abia and Ebonyi states of the Igbo culture area of Nigeria.